Perancangan Aplikasi Macro Untuk Meningkatkan Efisiensi Perencanaan Produksi Divisi PPIC - Mellisa Yang; Benedictus Rahardjo (Jurnal Titra, 2018)
Hapete is the best and most complete thread manufacturer in Indonesia. This company applies make to order production strategy. This production strategy makes the Production Planning and Inventory Control (PPIC) Division, the one who make the production planning, must have the efficient planning strategy. The program that PPIC Division use this time doesn’t really efficient, because of the big memory of the used program. The use of macro and Visual Basic Application (VBA) will reduce the memory of the program. The analyzing that has been done is comparing the memory between the new program and the old program. The old simulation program has 4657 KB as its memory, while the new program has 558 KB as its memory. The old planning program has 7969 KB as its memory, while the new program has 297 KB as its memory. The old monitoring program has 2906 KB as its memory, while the new program has 101 KB as its memory. The guide book has been made for further development of the program, which will make the easier development process for the program.